The impact of bariatric surgery on breathing-related polysomnography parameters—Updated systematic review and meta-analysis - Mashaqi, Saif; Rihawi, Anas; Rangan, Pooja; Ho, Katherine; Khokhar, Mateen; Helmick, Sonia; Ashouri, Yazan; Combs, Daniel; Ghaderi, Iman; Parthasarathy, Sairam (Frontiers in Sleep, 2023)
We conducted this systematic review and meta-analysis (SRMA) to evaluate the impact of bariatric surgery on obstructive sleep apnea (OSA) as represented by the following polysomnography (PSG) parameters: apnea-hypopnea index (AHI), oxygen desaturation index (ODI), mean oxygen desaturation (mean SpO2), total sleep time spent with SpO2 < 90% (T-90), and the nadir of oxygen saturation (L SpO2). A comprehensive search of the literature was conducted in Ovid MEDLINE, Embase, and Scopus, from inception to March 31, 2023. Only English written studies were reviewed. The analysis of all outcomes was performed using a random-effects model. We included 30 studies (two randomized controlled trials and 28 observational studies) in the final quantitative synthesis with a total of 1369 patients. We concluded that bariatric surgery (regardless of the type) was associated with reduction in AHI (MD 23.2 events/h (95%CI 19.7, 26.8), ODI (MD 26.8 events/h (95%CI 21.6, 32.1), mean SpO2 (MD -1.94 % (95%CI -2.5, -1.4), T-90 (MD 7.5 minutes (95%CI 5.0, 10.0) and L SpO2 (MD 9.0 % (95%CI -11.8, -6.3). Our SRMA results are updates to previously published results and continue to support the positive impact of bariatric surgery on OSA and sleep-related hypoxia.